The Role of Rotational Power and Mobility on Throwing Velocity - Talukdar, Kaushik (Auckland University of Technology, 2014)
The ability of players to consistently throw at high velocity with accuracy is considered to be a fundamental task influencing game outcomes in sports such as baseball and cricket. Throwing requires rotational power and mobility of the upper/lower limbs (in the transverse plane) for optimal execution. A clearer understanding of this kinetic chain promises to elucidate athlete’s deficiencies and guide future practitioner programming. A screening assessment battery that can diagnose strengths and weaknesses in this kinetic chain is of paramount importance. Therefore the initial objective of this thesis was to explore and review rotational power and mobility assessments such as medicine ball throw, chop and lift, seated hip and thoracic rotation range of motion (ROM). From the literature review it was surmised that these assessments were of great utility and for the most part considered reliable, though it was acknowledged that there was a paucity of research investigating the chop and lift, and no research had quantified both relative and absolute consistency between days in professional athletes. Furthermore, the influence of rotational power and mobility on functional performance was largely unexplored. These two findings provided the focus of the experimental chapters of this thesis. Following the review of literature, the interday reliability of chop and lift among professional cricketers was investigated. The absolute and relative consistency of the assessment using loads of 15% (chop) and 12% (lift) bodyweight were quantified. The lift (CV: 7.4%-16.3%, ICC: 0.74-0.94) was found to be more reliable between days compared to the chop (CV: 9.2%-19%, ICC: 0.54-0.83). It was suggested that further research on the chop assessment be undertaken given the limitations identified in this study. The aim of the final part of this thesis was to determine the influence of rotational mobility and power variables such as hip and thoracic rotation ROM, side medicine ball throw (seated and standing), seated cricket ball throw, chop and lift on cricket ball throwing velocity. The seated cricket ball throw was found to be significantly different (12.3%) between fast and slow throwers. Additionally, it was found that bilateral thoracic rotation ROM; hip external rotation ROM on the dominant side, force and work required in the chop was significantly different between fast and slow throwers. Faster throwers in this study displayed greater force (18.4%) and work (31.2%) outputs in the chop compared to slower throwers, however slower throwers showed significantly greater ROM in the thoracic (13.4% to 16.8%) and hip region (11.8%). Substantial (not significant) anthropometrical (height and mass) differences between the groups can be attributed to the differences observed in force and work outputs in chop and seated cricket ball throwing velocity. In conclusion, greater ROM at proximal regions such as hips and thoracic may not increase throwing velocity in cricket as reduced ROM at proximal regions can be useful in transferring the momentum from the lower extremity in an explosive task such as throwing. Future research should investigate both proximal and distal region contribution and thereafter assess the influence on cricket ball throwing velocity.
Keywords: Rotational training; Power; Mobility; Throwing; Velocity; Assessment